The Role of Notaries in Protecting Property Ownership Rights in Indonesia - Tjandraningsih, Dewi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to examine the role of notaries in protecting property ownership rights in Indonesia, particularly in the context of drafting authentic deeds as legally binding evidence. Notaries play a crucial role in ensuring the legality and legal certainty of property transactions, thus preventing disputes and fraud. The research method used is normative juridical, with a document study approach focusing on laws and regulations related to the notary profession and agrarian law in Indonesia. The results show that notaries have a strategic role in providing legal protection through the preparation of deeds that meet formal and material requirements, as well as providing legal explanations to parties involved in transactions. However, obstacles remain, such as insufficient supervision and limited public understanding of the notary’s functions, which weaken the protection of property ownership rights. Therefore, it is necessary to improve notaries' professionalism and legal education for the public to optimize the protection of property ownership rights.